2016
DOI: 10.1289/ehp212
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Fine Particulate Air Pollution Causes Vascular Insulin Resistance by Inducing Pulmonary Oxidative Stress

Abstract: Background:Epidemiological evidence suggests that exposure to ambient air fine particulate matter (PM2.5) increases the risk of developing type 2 diabetes and cardiovascular disease. However, the mechanisms underlying these effects of PM2.5 remain unclear.Objectives:We tested the hypothesis that PM2.5 exposure decreases vascular insulin sensitivity by inducing pulmonary oxidative stress.Methods:Mice fed control (10–13% kcal fat) and high-fat (60% kcal fat, HFD) diets, treated with 4-hydroxy-2,2,6,6-tetramethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 45 publications
(79 reference statements)
8
125
1
4
Order By: Relevance
“…A spillover effect is consistent with recent observations showing that oxidants generated in the lung by PM exposure could accelerate the formation of atherosclerotic lesions 147 and that increased superoxide dismutation in the lung could prevent PM-induced insulin resistance. 148 Additionally, activation of several lung receptors and nerve endings by PM could lead to change in heart rate, heart rate variability and electrocardiographic changes reflective of an increase in sympathetic tone. Such changes and the resulting hemodynamic and electrophysiological changes could account for the acute cardiovascular effects of PM.…”
Section: The Social Environmentmentioning
confidence: 99%
“…A spillover effect is consistent with recent observations showing that oxidants generated in the lung by PM exposure could accelerate the formation of atherosclerotic lesions 147 and that increased superoxide dismutation in the lung could prevent PM-induced insulin resistance. 148 Additionally, activation of several lung receptors and nerve endings by PM could lead to change in heart rate, heart rate variability and electrocardiographic changes reflective of an increase in sympathetic tone. Such changes and the resulting hemodynamic and electrophysiological changes could account for the acute cardiovascular effects of PM.…”
Section: The Social Environmentmentioning
confidence: 99%
“…In addition it has been suggested that ultrafine/nanosized particles or soluble particle constituents could enter the bloodstream and affect cardiovascular and metabolic health by direct interactions (Figure 1) [8]. This is supported by studies that show for instance the critical role of oxidative stress in mediating PM-induced vascular and metabolic dysfunction [17,18] and our recent studies that show that averting pulmonary oxidative stress prevented PM 2.5 -induced vascular inflammation and insulin resistance and restored endothelial progenitor cell number and function [13,19]. …”
Section: Introductionmentioning
confidence: 69%
“…Studies conducted in several countries, such as Europe, America, and Asia reported strong associations among exposure to air pollutants, insulin resistance, obesity, and diabetes with women overrepresented in the affected groups [165][166][167][168][169][170]. These findings have also been recapitulated in animal models, where exposure to particulate matter resulted in increased insulin resistance followed by a high-fat diet [171][172][173], and these effects were associated with inflammation triggered by mechanisms involving pulmonary oxidative stress [174].…”
Section: Outdoor Air Pollution and Lung Healthmentioning
confidence: 90%